Prevalence of bovine paratuberculosis in Chinese cattle populations: a meta-analysis - Huiying, Zhang; Mingfeng, Chu; Wei, Cheng; Shuiyun, Chen; Yuchen, Liang; Honghai, Wang; Xuelong, Chen; Yanping, Qi (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundBovine paratuberculosis is a chronic infectious disease of ruminants primarily caused by Mycobacterium avium subsp. paratuberculosis (MAP). It is essentially a chronic granulomatous enteritis characterized by intractable diarrhea, progressive lethargy, and thickening of the intestinal mucosa with the formation of crumpled pouches. Bovine paratuberculosis not only adversely affects milk production and the quality of dairy products but also poses a significant threat to the economic development of dairy farming and human food security. This systematic review and meta-analysis was conducted to assess the prevalence of MAP infection among cattle herds in mainland ChinaResultsA total of 62 studies with data from 102,340 cattle in 24 provinces in China were selected after matching the assessment criteria. In China, the overall estimated prevalence of MAP infection in cattle was 8%(7727/102340). Interestingly, the MAP infection rate in cattle in southern China was estimated to be 2% (6/281), which was significantly lower compared with other regions of China, and the highest infection rate was 12% (1914/16008) in eastern China. MAP infection rates were related to age, average herd size, type of use, season, detection method, and sample type. Moreover, the MAP infection rate in cattle did not correlate with the publication date of the studies.ConclusionThe analysis identified age, average herd size, type of use, and season as significant potential risk factors associated with PTB pool positivity. In addition, the detection method and sample type can also potentially affect the incidence of detected PTB.